2014
DOI: 10.3747/co.21.1671
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular–to–Body Cell Mass Ratio and Subjective Global Assessment in Head-and-Neck Cancers

Abstract: Background: The ratio of extracellular mass to body cell mass (ecm/bcm), determined by bioelectrical impedance analysis, has been found to be a potentially useful indicator of nutrition status. Subjective global assessment (sga) is a subjective method of evaluating nutrition status in head-and-neck cancer. The present study was conducted to investigate the association between ecm/bcm and sga in head-and-neck cancer. Methods: Patients were classified as either well-nourished or malnourished by sga. Bioelectrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…It has been formerly found to be a useful predictor of malnutrition in cancer patients. 25 The number of malnourished patients in our study cohort was comparable to those reported elsewhere. 5 One of the possible factors contributing to malnutrition in post-LT CF patients is inadequately treated or underdiagnosed endocrine and/or exocrine PI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been formerly found to be a useful predictor of malnutrition in cancer patients. 25 The number of malnourished patients in our study cohort was comparable to those reported elsewhere. 5 One of the possible factors contributing to malnutrition in post-LT CF patients is inadequately treated or underdiagnosed endocrine and/or exocrine PI.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, a rising ECM/BCM ratio is an early warning sign of a worsening nutritional status. It has been formerly found to be a useful predictor of malnutrition in cancer patients 25 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that patients with a high fat-free mass index (FFMI) (calculated from fat-free mass/weight) had a significantly better prognosis than did patients with a low FFMI [9][10][11]. Recently, it has been used for clinical assessment of the phase angle (PhA) [8][9][10][11], extracellular water (ECW), intracellular water (ICW) [10,12], body cell mass (BCM) [12,13] and different compartments ratios [4,14]. The PhA is a non-invasive simple measure directly retrieved from resistance (R) and reactance (Xc) raw data [9][10][11], which appears to be even more interesting for cancer survival [9,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…The ECM/BCM ratio was also evaluated in a study including 75 patients with head and neck cancer and they were divided into well-nourished and malnourished groups based on the subjective global assessment procedure. 35 Similar to the pancreatic cancer study, patients with a lower ECM/BCM ratio were significantly better nourished with a cutoff value for classification as malnourished determined to be 1.194 or higher. This cutoff value for head and neck cancer was determined to be 76% sensitive and 63% specific in detecting malnourishment in this patient population.…”
Section: Evaluation Of Nutritional Status Using Bia Measuresmentioning
confidence: 88%